Kids Bakery (Services) /Izzati Amani Mohd Mazlan ... [et al.] - Izzati Amani, Mohd Mazlan; Nur Irdyna Syafiqah, Ahmad Syukry; Siti Nursyakina, Ratief; Nursabrina, Azali (2019)
This KIDS Bakery is categories as private company. This is because this company refers to a company that performs services in exchange for other goods nd services or money. as example in our bakery we produce several cakes,sweet and pastries to be sell and gain profit from it.